Using the Science Technology and Society approach: A dynamic and playful approach from a meaningful learning perspective in elementary school (Research, Society and Development, 2020)
This paper aims to analyze the implementation of a Science, Technology and Society (STC) approach in primary school, seeking to highlight and reflect the teaching practice for meaningful learning and its contribution to student education as a citizen. This research was idealized through the construction of a study group with students of the 9th grade of the final years of elementary school at the Paulo Aragão School of Sobral, CE. In this article, we show through a qualitative research, the point of view of the teachers responsible for the construction of the study group, reporting the difficulties and results with the use of the CTS approach and their respective approaches, with social sphere themes merged with the studied contents. in the classroom, bringing contributions to a learning method differently from the traditional, and should be used as a teaching tool that provides students with meaningful learning.